The Intimate Connection Between Lipids and Hedgehog Signaling - Nguyen, Thi D.; Truong, Melissa E.; Reiter, Jeremy F. (Frontiers in Cell and Developmental Biology, 2022)
Hedgehog (HH) signaling is an intercellular communication pathway involved in directing the development and homeostasis of metazoans. HH signaling depends on lipids that covalently modify HH proteins and participate in signal transduction downstream. In many animals, the HH pathway requires the primary cilium, an organelle with a specialized protein and lipid composition. Here, we review the intimate connection between HH signaling and lipids. We highlight how lipids in the primary cilium can create a specialized microenvironment to facilitate signaling, and how HH and components of the HH signal transduction pathway use lipids to communicate between cells.